L’inventaire du patrimoine culturel immatériel hospitalier. Une histoire de résilience(s) - Yann Leborgne (In Situ)
At a time when university hospitals are experiencing significant economic and organisational changes, the CHU of Rouen has committed itself to carrying out an inventory of its intangible cultural heritage. The project was initiated by the hospital’s cultural delegation with the support of the regional cultural services (DRAC Normandie). This project was not considered merely as a measure of heritage safeguarding, nor as the recognition of the constituent parts of the hospital community’s identity. Based on the voluntary participation of many members of the hospital staff, it sought to answer the existential questions that surround the meaning of their everyday life practices. Though this undertaking was established over the long-term, according to its ambition and the vast scale of the territory concerned, this article looks back on an approach that underlines the operational aspects of an inventory of the intangible cultural heritage. Treated as a form of introspection and recognition, the inventory became invested by the hospital community in order to help it overcome the pain, when changes lead to questions about inner principles and values. The intangible cultural heritage emerged as a cure taking part in a process of resilience.